Residents' Benefits Evaluation of Urban Development Plans - A Willingnes-To-Accept Model for a Multi-functional Land Use Project in Amsterdam - Caroline A. Rodenburg; Peter Nijkamp; Henri L.F. de Groot; Erik T. Verhoef (Tinbergen Institute, 2009)
Urban re-development projects may generate various positive as well as negative spatial externalities to the existing population in a given area. This study aims to assess the order of magnitude of the expected net benefits for incumbent residents from a large scale project in the Southern part of Amsterdam (the Netherlands), which is planned to transform the area into a large multi-functional urban centre. We employ a specific stated preference method (viz. a willingness-to-accept method) to assess the net socio-economic benefits for the population in the area concerned. Our approach explicitly considers perceived costs and benefits in the foreseen ,,end-states? as well as those incurred during the transitional (construction) phase towards such end-states. It is concluded that the multi-functional urban re-development project under consideration is not supported by the residents in the area, as the long-run benefits are perceived to be overshadowed by the short-run environmental nuisances.
Keywords: Q15; R52; O18; 330; multi-functional land use; stated preference; urban development; Städtische Flächennutzung; Willingness to pay; Stadtentwicklung; Amsterdam; Niederlande